Análisis técnico del diseño de alumbrado eléctrico de la avenida Miguel Yunez (la Urb. La Castilla- Redondel) Samborondón-Guayaquil - Moreira Alcantara, Diego Kerwin (2021)
This research work aims to know the different ways to create a public lighting system, the one of the most suitable and efficient lamp, the correct location of the lighting poles will also demonstrate the different types of luminaires that exist in the market comparing its energy efficiency, electrical design of the luminaires, costs of the different facilities, duration of the ratorials, dispersion, scope, control, trying to find the best option to achieve positive changes in the public lighting of Avenida MIGUEL YUNEZ (LA URBANIZACION. CASTILLA – REDONDEL) The avenue, MIGUEL YUNES, is known for being one of the main entrance arteries to GUAYAQUIL, so it seeks to update the public lighting system in order to improve the visualization of its surroundings. In the current lighting of the road it is observed that mercury lamps are installed so that These were the most used in ancient times, it is known that they generate pollution since at the time of their elimination the gas in the lamp is very polluting, therefore, a change in design and the cleaner and more efficient technology such as lamps are sought . Sodium and Led lamps, saving maintenance costs and energy costs. Emphasis is placed on LED technology for the illumination of the avenues of the mutopista Hopes that it will provide theoretical and uronic data, achieving the correct update of the Existing systems for public lighting